A Convenient and Efficient One-Pot Synthesis of Arylacetones from (E)-3-Aryl-2-methylacrylic Acids by Curtius Rearrangement - He, Xin; Cao, Chong; Liang, Jingwei; Li, Xinyang; Zhang, Tingjian; Meng, Fanhao (Synlett, 2017)
A convenient and efficient method was developed for the synthesis of arylacetones from (E)-3-aryl-2-methylacrylic acids through a Curtius rearrangement. The Curtius rearrangement of (E)-3-aryl-2-methylacryloyl azides and subsequent hydrolysis proceeded at mild temperatures in a two-phase medium of carbon tetrachloride and water containing a catalytic amount of tetrabutylammonium bromide to give the corresponding derivatives in 82–93% yield.
Keywords: arylacetones; Curtius rearrangement; methylarylacrylic acids; phase-transfer catalysis; acryloyl azides